El proceso de formación de agenda y formulación de la política de lucha contra el contrabando (2010-2015) : entre la productividad, competitividad y el crimen organizado (2017)
The problem of smuggling in Colombia is not a recent illegal phenomenon. However, and as a result of the decisions taken by the country in terms of productivity and competitiveness, during the last eight years, this problem has gained increasing relevance in the public agenda. Thus, this document focuses on the public policy against smuggling in Colombia during the period 2010 to 2015, and analyzes how the governmental agenda is set and how choices are made. Through the Garbage Can Model and its analysis of organized anarchies, the paper provides evidence of those institutional elements that allows organizations and its members to adopt certain decisions towards the smuggling policy problem. Furthermore, and taking into account John Kingdons' framework, this article demonstrates how actors identify, propose and prioritize solutions as well as recognize opportunities and build up alliances, elements which determine the way the problem of smuggling in Colombia is define, impulse and affected.